2007
DOI: 10.1152/ajplung.00345.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple MAPK-mediated transcription factors regulated by tobacco smoke in airway epithelial cells

Abstract: May 11, 2007; doi:10.1152/ajplung.00345.2006.-Activation and regulation of transcription factors (TFs) are the major mechanisms regulating changes in gene expression upon environmental exposure. Tobacco smoke (TS) is a complex mixture of chemicals, each of which could act through different signal cascades, leading to the regulation of distinct TFs and alterations in subsequent gene expression. We proposed that TS exposure affects inflammatory gene expression at the transcriptional level by modulating the DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…These results bring up the speculation that NF-kB is important for early cellular recruitment, and that MAPKs are important for subsequent cellular influx. These findings are consistent with previous reports indicating that the activation of NF-kB and MAPKs in the lungs occurs at different concentrations of mainstream smoke exposure (63,64). However, our findings are the first, to the best of our knowledge, to show the regulation of NF-kB and MAPKs by CXCL5 in the lungs during SHS exposure.…”
Section: Discussionsupporting
confidence: 93%
“…These results bring up the speculation that NF-kB is important for early cellular recruitment, and that MAPKs are important for subsequent cellular influx. These findings are consistent with previous reports indicating that the activation of NF-kB and MAPKs in the lungs occurs at different concentrations of mainstream smoke exposure (63,64). However, our findings are the first, to the best of our knowledge, to show the regulation of NF-kB and MAPKs by CXCL5 in the lungs during SHS exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Some reports demonstrated induction, whereas others found inhibition or no effect. Low-level NF-kB induction in isolated cells by cigarette smoke was often demonstrated with subconfluent cell testing, low smoke preparation concentrations, or shorter durations of exposure (28,33,39,40). In contrast, the impairment of NF-kB activation or function was often associated with confluent cells or treatment with higher levels of exposure to cigarette smoke, alone or in combination with other stimuli (28,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Yagi et al [95] demonstrated by immunohistochemistry that airway epithelial cells from ex-smokers with or without COPD also have elevated activation of NF-jB, since increased phosphorylated IjB-a was found. Although most of the studies have demonstrated that increased NF-jB activation is dependent on IKK activation, Zhao et al [96] showed a novel mechanism of NF-jB activation modulated by tobacco smoke. These authors revealed that in A549 cells, a human lung cancer cell line, tobacco smoke exposure significantly induces the microtubule-associated protein kinase (MAPK) signaling pathway via activation of extracellular signal-regulated kinases 1 and 2 (ERK1/ERK2), resulting in direct IjB phosphorylation and NF-jB activation.…”
Section: Effect Of Smoking On Immune-inflammatory Mediatorsmentioning
confidence: 99%
“…1. Besides NF-jB, Zhao et al [96], using a protein/DNA array approach, identified 19 other transcriptional factors regulated by tobacco smoke. Among these are GATA, PAX5, and Smad 3/4 that were significantly stimulated by tobacco smoke, and ISRE and ICSBP that had their DNA-binding activities significantly decreased after tobacco smoke treatment.…”
Section: Effect Of Smoking On Immune-inflammatory Mediatorsmentioning
confidence: 99%